2022
DOI: 10.3389/fpsyg.2022.986800
|View full text |Cite
|
Sign up to set email alerts
|

A study on psychological determinants of users' autonomous vehicles adoption from anthropomorphism and UTAUT perspectives

Abstract: As the autonomous vehicles technology gradually enters the public eye, understanding consumers' psychological motivations for accepting autonomous vehicles is critical for the development of autonomous vehicles and society. Previously, researchers have explored the determinants of fully autonomous vehicles but the relevant research is far from enough. Moreover, the relationship between anthropomorphism and users' behavior has been ignored to a large extent. Therefore, this study aim to fill the gap by using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…Perceived AI Intelligence (PAI) and Metacognitive Self-Regulated Learning (MSR): The survey strongly supported this hypothesis, demonstrating that perceived AI intelligence strongly affects instructors' MSR [ 95 ]. In interviews, educators said AI's intelligence helped them encourage self-regulated learning.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived AI Intelligence (PAI) and Metacognitive Self-Regulated Learning (MSR): The survey strongly supported this hypothesis, demonstrating that perceived AI intelligence strongly affects instructors' MSR [ 95 ]. In interviews, educators said AI's intelligence helped them encourage self-regulated learning.…”
Section: Discussionmentioning
confidence: 99%
“…According to earlier research, people are more likely to embrace and keep using new technology if they see that it has benefits that outweigh its drawbacks ( Venkatesh et al, 2003 , 2012 ). Additionally, numerous research findings indicate that PE has a significant impact on people’s propensity to use certain products or services ( Williams et al, 2015 ; Hoque and Sorwar, 2017 ; Chao, 2019 ; Nan et al, 2022 ; Tian and Wang, 2022 ). For example, Chao (2019) reported a study on the use of mobile learning on the basis of the UTAUT model, and the author showed that PE has a significantly positive impact on behavioral intention with a coefficient of 0.18.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“… Nan et al (2022) studied the intention of using face recognition payment and also found a positive effect of PE on behavioral intention with a coefficient of 0.27. Tian and Wang (2022) found that the intention to adopt autonomous vehicles could be indirectly influenced by performance expectancy through perceived value. On the other hand, the antecedents of PE are in fact less understood, and existing studies have clearly indicated that risk and trust are two important factors determining behavioral intentions in various finance-related contexts ( Gu et al, 2009 ; Slade et al, 2015 ; Kaur and Arora, 2020 ; Nan et al, 2022 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…It is extremely important to carry out research on users' psychological factors [39]. Although research on user behavior of driverless cars has gradually attracted attention, the psychological factors were focused on only in a small number of previous studies [35,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many current studies investigating users' behavioral intentions for autonomous vehicles, they are still not comprehensive [39]. The current research on the behavioral intention of autonomous vehicles has problems such as the use motivation is not unified [58].…”
Section: Introductionmentioning
confidence: 99%